Mathematical Analysis of the Effects of Population Heterogeneity on Disease-Induced Herd Immunity to Covid-19 - Rahimi, Hezbullah (Journal of Natural Sciences – Kabul University, 2024)
Despite strict preventive measures, most countries were seriously affected by the outbreak of Covid-19. Using a Modified SEIR model, it has been shown that population heterogeneity can significantly affect the overall immunity from the disease because the proportion of infected people is higher in groups with the highest contact rate than in groups with a low contact rate. It is stated in this article, if the basic number of secondary production , for a society in which social activities are considered different according to age, is equal to , then the overall immunity level due to the disease can be , which is Considerably less than the classical immunity level of for a uniformly vaccinated population. The purpose of this review is to understand the complex mechanism of heterogeneous population and its significant effects to achieve herd immunity caused by the covid-19 virus.